EFFECT OF BIO-FERTILIZER ON INNOVATION ATTRIBUTES OF FARMERS (Journal of Plant Disease Sciences, 2017)
The study was conducted in Wardha district of Maharashtra State where front line  demonstrations on seed treatment in soybean with bio-fertilizers were conducted by Krishi  Vigyan Kendra on farmer's field. Fifty FLDs were evaluated to assess the impact of bio fertilizers on adoption and relative advantage, compatibility, complexity and suitability of  the technology. Seed treatment of bio-fertilizer in soybean gave 56.93 per cent more yield as  compare to untreated seed plot. In the compatibility studies, cent per cent farmers reported  that this technology is suitable to agro-climatic conditions, consistent with existing situation  and compatible with norms of soybean cultivation. Over 90.00 per cent respondents accepted  that it meets felt need of farmers. In the categorization, majority of respondents were found to  be taken high relative advantage, highly compatible, low complexity and high suitability.  The total, effectiveness of bio-fertilizers was found to be 91.96 per cent. Regarding impact on  adoption, most of the respondents (68.00%) were accepted the technology, but some of them  were not able to adopt due to some constraints faced by farmers such as availability of bio  fertilizers, make hands and cloths darken during seed treatment and irritation in their eyes.  The relational analysis, relative advantage and suitability were positive and highly  significant whereas, complexity was highly but negatively correlated with the adoption.
Keywords: Impact, FLD, Seed treatment, Biofertilizer, adoption